28. THE EMPLOYMENT STATUS OF BACHELOR OF NUTRITION IN VIETNAM IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) Describing the employment status of Bachelor of Nutrition, (2) Describing jobposition suitability and the difficulties of Bachelor of Nutrition faced when working in field ofclinical nutrition.Methods: A cross-sectional study, using an online survey conducted on 278 subjects of 6 Bachelorof Nutrition courses graduated in Hanoi Medical University.Results: The highest percentage of nutrition bachelors working at hospitals accounted for 37% andtends to decrease from course I to course VI. Professional suitability with job positions is highlyappreciated in nutrition departments, nutrition clinics/consultants, and food processing companies.The difficulties that BN faced in field of clinical nutrition is not being able to participate in nutritionconsultations, not being examined and assessed nutrition status for patients.Conclusion: The most of Bachelor of Nutrition are working on field of clinical nutrition, and onfields suitable for their profession. However, they have faced many limitations due to the lack ofpolicies regulating functions and tasks on professional activities
Keywords: Employment status, Bachelor of Nutrition, clinical nutrition.